2019
DOI: 10.1155/2019/4736203
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA FEZF1-AS1 Promotes TGF-β2-Mediated Proliferation and Migration in Human Lens Epithelial Cells SRA01/04

Abstract: Posterior capsule opacification (PCO) is a common complication after cataract surgery attributed to the proliferation and migration of postoperative residual lens epithelial cells (LECs). The long noncoding RNA (lncRNA) FEZ family zinc finger 1 antisense RNA 1 (FEZF1-AS1) promotes the proliferation and migration of multiple types of cancer cells. Here, we discovered that FEZF1-AS1 is markedly upregulated in TGF-β2-treated SRA01/04 cells. In addition, the proliferation and migration of SRA01/04 cells were enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The limitation of this study is that although the TGF-β2induced SRA01/04 cell line is a common in vitro cell model for PCO research (Wang et al, 2019;Zhang et al, 2018), it may not reflect normal lens biology because it does not express many normal lens markers; thus, we cannot determine whether there are potential regulatory differences when compared with the normal lens (Weatherbee et al, 2019). Besides, we only verified the regulatory axis at the cellular level, but not in the animal model.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The limitation of this study is that although the TGF-β2induced SRA01/04 cell line is a common in vitro cell model for PCO research (Wang et al, 2019;Zhang et al, 2018), it may not reflect normal lens biology because it does not express many normal lens markers; thus, we cannot determine whether there are potential regulatory differences when compared with the normal lens (Weatherbee et al, 2019). Besides, we only verified the regulatory axis at the cellular level, but not in the animal model.…”
Section: Discussionmentioning
confidence: 93%
“…Besides, TGF-β2 is the primary subtype of the TGF-β family in aqueous humor (Dong, 2020;Zhang et al, 2017). Therefore, TGF-β2induced human lens epithelial cells (HLECs) can be used to simulate the PCO microenvironment (Wang et al, 2019;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the proliferation of lens epithelial cells was associated with the occurrence and development of cataract [ 30 ]. There is also study revealed that the proliferation of lens epithelial cells could induce the occurrence and development of cataract [ 31 ]. We also revealed that the inhibition of TRIM22 rescued the proliferation of lens epithelial cells stimulated by H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…As an example, the elevated KCNQ1OT1 positively regulated SMAD4 expression to promote LEC proliferation and EMT in PCO [31]. LncFEZF1-AS1 promoted the proliferation and migration via upregulating FEZF1 expression in PCO [39]. Upregulated MALAT1 can activate p38, a component of mitogen-activated protein kinases (MAPKs) pathway, resulting in HLECs apoptosis in DC.…”
Section: The Expression and Function Of Lncrnas In The Cataractmentioning
confidence: 99%